The Association Between Estrogen-Containing Oral Contraceptive Pills and Hypothyroidism - Lama Alkahlout; Shahd Hamran; Nour Darwish; Yara Dweidri; Giridhara R. Babu; Rafif Mahmood Al Saady (International Journal of Endocrinology)
Conclusion: This study offers evidence that SHBG levels can be used to indicate estrogen-containing OCP use. Furthermore, higher SHBG levels are associated with higher odds of hypothyroidism among OCP users, and the odds of hypothyroidism vary across different ethnicities. These findings highlight the need for further research to explore the mechanisms linking OCP use to thyroid dysfunction and to investigate other potential risk factors.